Understanding and evaluating Trump's foreign policy: a three frame analysis. Issue 4 (3rd July 2020) - Steff, Reuben; Tidwell, Alan
ABSTRACT: Amidst the cacophony of the Trump presidency, is it possible to unearth the logic behind his foreign policy? Do his strategy and tactics stem from him or are they a response to the changing international structure? This article addresses these questions and seeks to evaluate the Trump administration's foreign policy record on its own terms by examining his methods and objectives through three frames: 'Art of the Deal', 'Make America Great Again', and 'Stable Genius'. By applying these frameworks to three cases: (1) migration, (2) NATO funding and (3) trade, the article finds that, in general, the policies and methods of the administration have been unable to achieve the President's stated goals in the global arena. In conducting this analysis and evaluation, the article makes a novel contribution to understanding the policy and philosophy of the Trump administration's foreign policy and enhances understanding of the policy outcomes that US diplomacy is attempting to achieve.